2021
DOI: 10.1002/hsr2.378
|View full text |Cite
|
Sign up to set email alerts
|

Goal attainment scaling for patients with low back pain in rehabilitation: A systematic review

Abstract: Background and aims: Goal attainment scaling (GAS) has been widely applied to chronic conditions; however, only recently has it been used for patients with low back pain (LBP). The objectives of this systematic review were to (a) examine the characteristics and rigor of published studies of GAS in the rehabilitation of patients with LBP, (b) describe how GAS has been applied in patients with LBP, and (c) evaluate the responsiveness and validity of GAS as an outcome measure in patients with LBP.Methods: A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…GAS may have therapeutic effects independent of intervention effects [21, 54]. For example, Herdman et al [21] found that clinically meaningful gains were found in both intervention and non-intervention groups using GAS in a memory and aging program.…”
Section: Discussionmentioning
confidence: 99%
“…GAS may have therapeutic effects independent of intervention effects [21, 54]. For example, Herdman et al [21] found that clinically meaningful gains were found in both intervention and non-intervention groups using GAS in a memory and aging program.…”
Section: Discussionmentioning
confidence: 99%
“…An exception was “ViViRa bei RĂŒckenschmerzen,” where the goal was performance enhancement. A systematic review by Haladay et al [ 32 ] shows that individual, patient-centered goals would be a useful addition to classic goals such as pain reduction. Apps should offer functions to formulate and track such goals.…”
Section: Discussionmentioning
confidence: 99%
“…GAS was first introduced by Kiresuk and Sherman in 1968 to evaluate outcomes in a mental health setting [ 7 ]. Since then, it has been successfully adapted for use in many other domains, including stroke rehabilitation [ 8 , 9 ], drug trials [ 2 ], back pain [ 10 ], rehabilitation [ 3 ], communication disorders [ 11 ], and in other older adults with dementia [ 1 ], and complex needs [ 12 ]. There is growing evidence that GAS is sensitive to change and can capture clinically meaningful changes that often are ignored or are not elicited by standardized tests [ 6 ].…”
Section: Introductionmentioning
confidence: 99%